(untitled) (The Research of Medical Science Review, 2025)
Objectives: To determine the effect of adjuvant “pudendal nerve block” in post-operative pain following perianal surgery for non-suppurative conditions. Study design: Quasi-experimental study. Place and duration of study: “Nov 24 to April 25,CMH Abbotabad Methodology: 66 patients who were planned to undergo elective perianal surgery were included in the study and were divided into “Pudendal nerve block + spinal anesthesia group” and “spinal anesthesia alone group” alternatively in order of presentation. Post-operative outcomes were compared between groups. Data was analyzed by SPSS 20.00. Results: Mean age was 36.94 ± 7.85 years. There were 42 (63.64%) males and 24 (36.36%) females. Mean BMI was 32.71 ± 6.96 kg/m2. Frequency of patients who had requirement of additional post-operative analgesia during 24-hours after surgery in “pudendal nerve block + spinal anesthesia group” was 5 (15.15%) while in “spinal anesthesia alone group” it was 20 (60.61%), (p < 0.001). Frequency of patients who were pain free after 24 hours of surgery in “pudendal nerve block + spinal anesthesia group” was 20 (60.61%) while in “spinal anesthesia alone group” it was 7 (21.21%), (p = 0.001). Conclusion: “Pudendal nerve block” can serve as a highly useful adjuvant to “spinal anesthesia (SA)” in patients who undergo perianal surgeries